2014
DOI: 10.1111/eci.12286
|View full text |Cite
|
Sign up to set email alerts
|

Primary aldosteronism in hypertensive patients: clinical implications and target therapy

Abstract: Using the FDST, an increased prevalence of PA in hypertensives was observed. Α significant blood pressure lowering effect was obtained with MRA treatment, implying that these agents may be beneficial in a significant number of hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
5
16
0
Order By: Relevance
“…These results suggest that dexamethasone administration is expected to have a similar beneficial effect on the performance characteristics of FST and support the view that both the ACTH and renin stimulatory effects on aldosterone secretion need to be considered for making the diagnosis (60,61). These results have recently been confirmed by expanding our initial study including a much higher number of individuals (327 hypertensive and 100 controls) (78).…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensionsupporting
confidence: 76%
See 2 more Smart Citations
“…These results suggest that dexamethasone administration is expected to have a similar beneficial effect on the performance characteristics of FST and support the view that both the ACTH and renin stimulatory effects on aldosterone secretion need to be considered for making the diagnosis (60,61). These results have recently been confirmed by expanding our initial study including a much higher number of individuals (327 hypertensive and 100 controls) (78).…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensionsupporting
confidence: 76%
“…Similarly, the cut-off value of post-FDST ARR was also lower (26 pmol/mU vs 32 pmol/mU), whereas the post-FDST aldosterone levels were higher (82 pmol/l vs 74 pmol/l) albeit without alteration in the prevalence of PA that was found to be 29% (78). The observed different test characteristics in the last study may be attributed to the higher number of controls included and the stricter selection criteria adopted.…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some authors found that 47% of patients suffering from PA had ARR above 30 [30] (usually taken as the cut-off level) and 28% of those patients had ARR above 50 [31]. In our study it was found that the ARR above 8.25 supports the diagnosis of primary aldosteronism.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, in the present study, the maximum dose of MRAs used was up to 100 mg, whereas other studies have used higher doses of up to 200 mg (27). Previous studies performed in our unit have revealed that the prevalence of PA in unselected patients with hypertension ranges from 29 -32% (3,28), which added to the 27% prevalence of ALD hyper-response to stress, found in the present study, account for approximately 60% of patients with apparent ESHT expected to respond to MRAs. This figure is close to that of patients responding to eplerenone in the Levy et al study.…”
Section: Discussionmentioning
confidence: 64%